Electroporation with Calcium or Bleomycin: First Application in an In Vivo Uveal Melanoma Patient-Derived Xenograft Model - Ralitsa Anastasova; Miltiadis Fiorentzis; Hongtao Liu; Sami Dalbah; Nikolaos E. Bechrakis; Berthold Seitz; Utta Berchner-Pfannschmidt; Theodora Tsimpaki (MDPI AG, 2024)
Uveal melanoma (UM) represents a rare tumor of the uveal tract and is associated with a poor prognosis due to the high risk of metastasis. Despite advances in the treatment of UM, the mortality rate remains high, dictating an urgent need for novel therapeutic strategies. The current study introduces the first in vivo analysis of the therapeutic potential of calcium electroporation (CaEP) compared with electrochemotherapy (ECT) with bleomycin in a patient-derived xenograft (PDX) model based on the chorioallantoic membrane (CAM) assay. The experiments were conducted as monotherapy with either 5 or 10 mM calcium chloride or 1 or 2.5 µg/mL bleomycin in combination with EP or EP alone. CaEP and ECT induced a similar reduction in proliferative activity, neovascularization, and melanocytic expansion. A dose-dependent effect of CaEP triggered a significant induction of necrosis, whereas ECT application of 1 µg/mL bleomycin resulted in a significantly increased apoptotic response compared with untreated tumor grafts. Our results outline the prospective use of CaEP and ECT with bleomycin as an adjuvant treatment of UM, facilitating adequate local tumor control and potentially an improvement in metastatic and overall survival rates.